Quality circles: A managerial response to the productivity problem - L. J. Smalley; H. J. Bocker (South African Journal of Business Management, 1982)
The purpose of this article is to outline the development of the quality circle (QC) philosophy, its benefits and problem areas in which it can be applied, with reference to both theory and practical application. The QC organizational structure and special functions of the groups, individuals and committees involved in the process are also discussed. The groups comprise the members, leaders, staff for technical support, facilitators (or coordinators), middle and top management, steering and advisory committees and union officials. A process flow diagram is used to represent a model of the QC flow for one complete operating cycle. It shows the various interdependencies of all the groups involved and how this system actually functions.
Keywords: 650